I'm trying to solve below exercise, i.e.,

Let $(u_n) \subset \mathbb R$ and $(t_n) \subset \mathbb R_{>0}$ such that $(t_n)$ is non-decreasing. Assume that $$ (t_n u_n-t_m u_m)(u_n-u_m) \le 0 \quad \forall m, n \in \mathbb N. $$ Then $(u_n)$ is convergent.

  1. Could you have a check on my below attempt?
  2. Is there a more direct approach?

Thank you so much for your elaboration!

We have $$ \begin{aligned} & (t_{n+1} u_{n+1}-t_n u_n)(u_{n+1}-u_n) \le 0 \\ \iff & (u_{n+1}-u_n)^2 \le \frac{t_{n} - t_{n+1}}{t_{n+1}} (u_{n+1}-u_n) u_n. \end{aligned} $$

If $t_{n} - t_{n+1}=0$ then $u_{n+1} = u_n$. Let $t_{n} - t_{n+1}<0$. Because $(t_n)$ is non-decreasing, $\frac{|t_{n} - t_{n+1}|}{t_{n+1}} \le 1$ and thus $|u_{n+1}-u_n| \le |u_n|$. We have three cases, i.e.,

  1. If $u_n=0$ then $u_{n+1}=0$.
  2. If $u_n>0$ then $u_{n+1} \le u_n$. On the other hand, $|u_{n+1}-u_n| \le |u_n|$. So $0 \le u_{n+1} \le u_n$.
  3. If $u_n<0$ then $u_{n+1} \ge u_n$. On the other hand, $|u_{n+1}-u_n| \le |u_n|$. So $u_n \le u_{n+1} \le 0$.

It follows that

  • if $u_0=0$, then $u_n=0$ for all $n$.
  • if $u_0>0$, then $(u_n) \subset \mathbb R_{>0}$ is decreasing.
  • if $u_0<0$, then $(u_n) \subset \mathbb R_{<0}$ is increasing.

Thus $(u_n)$ is convergent.


1 Answer 1


Your proof is correct. Instead of taking absolute values one can also rewrite the given inequality as $$ t_n u_n^2 + t_m u_m^2 \le (t_n + t_m) u_n u_m \, , $$ which implies that $u_n$ and $u_m$ are both zero or both positive or both negative, so that the $u_n$ are all zero or all positive or all negative.

Then $$ 0 \le t_{n+1}(u_{n+1}-u_n)^2 \le (t_{n+1}-t_n) u_n (u_n-u_{n+1}) $$ implies that $u_n$ and $u_n-u_{n+1}$ have the same sign, so that (as you correctly concluded) the sequence is identically zero, or positive and decreasing, or negative and increasing.


You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .